Interactions of HIV and Antiretroviral Therapy With Neutrophils and Platelets - Madzime, Morris; Rossouw, Theresa M.; Theron, Annette J.; Anderson, Ronald; Steel, Helen C. (Frontiers in Immunology, 2021)
This review discusses the role of neutrophils and platelets in HIV transmission and disease, as well as the effect of HIV and the most common antiretroviral agents on the numbers and functions of these cells, as well as on neutrophil-platelet interactions. Neutrophils are important components of the innate immune system that mediate pathogen defense by multiple processes including phagocytosis, release of proteolytic enzymes, production of reactive oxygen species and neutrophil extracellular trap formation. Abnormalities of neutrophil count and function have been described in the setting of HIV infection. The majority of antiretroviral agents, with the exception of zidovudine, have been reported to correct neutropenia. Question still remain about their impact on neutrophil function and the possibility of persistent neutrophil activation, which could predispose people living with HIV to chronic inflammatory disorders even in the presence of virally suppressive treatment. The effects of protease inhibitors and integrase strand transfer inhibitors on neutrophil function are also still poorly understood and deserve further study. Besides mediating hemostatic functions, platelets are increasingly recognized as critical role players in the immune response against infection. In the setting of HIV, these cells have been found to harbor the virus even in the presence of antiretroviral therapy, hence potentially promoting viral dissemination. While HIV-infected individuals often present with thrombocytopenia, they have also been reported to have increased platelet activation, as measured by an upregulation of expression of CD62P (P-selectin), CD40 ligand, glycoprotein IV and RANTES. Despite antiretroviral treatment-mediated viral suppression, HIV-infected individuals reportedly have sustained platelet activation and dysfunction, contributing to persistent immune activation and an inflammatory vascular environment. These factors can increase the risk for comorbidities such as cardiovascular disease, which has become the leading cause of morbidity and mortality in HIV-infected individuals on treatment. How these effects may be mediated by neutrophil-platelet interactions and the proinflammatory effects of tobacco use, are poorly understood and deserve further study. Specific attention should be paid to the effect of abacavir and ritonavir boosted lopinavir and darunavir, all of which have been linked to an increased risk of cardiovascular disease.